2017
DOI: 10.1017/s1352465816000552
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Evaluation of a Strengths-Based CBT Intervention Module with College Students

Abstract: The PMR is a promising intervention module. It requires further evaluation in clinical contexts, with larger samples, and long-term follow-up assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(7 citation statements)
references
References 9 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…The results of this study are consistent with previous findings on the PMR: As an option to bridge the waiting time for therapy, the PMR has been shown to be useful as a three-session group intervention [22]. In a study with distressed students in need for counseling, the PMR in a face-to-face setting was superior to a matched control group [23]. In a third study comparing the PMR to a three-session cognitive ABC intervention sensu Ellis [60], the PMR was at least equally effective, and at the same time superior to an untreated control group [61].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are consistent with previous findings on the PMR: As an option to bridge the waiting time for therapy, the PMR has been shown to be useful as a three-session group intervention [22]. In a study with distressed students in need for counseling, the PMR in a face-to-face setting was superior to a matched control group [23]. In a third study comparing the PMR to a three-session cognitive ABC intervention sensu Ellis [60], the PMR was at least equally effective, and at the same time superior to an untreated control group [61].…”
Section: Discussionsupporting
confidence: 89%
“…Unlike other effective resilience interventions that focus on establishing new coping strategies [21], the PMR uses strategies that are already available to an individual. In initial studies, the PMR has been shown to be useful while waiting for a therapy [22] or for student counseling [23] where it was administered in three sessions either as group or individual therapy. With small to large effect sizes on dimensions of psychopathology, self-esteem, optimism and well-being, it seems to have a broad outcome profile.…”
Section: Generalize Them To Different Areas Of Lifementioning
confidence: 99%
“…A significant effect was found also on hope, but not on the amount of self-reported positive or negative affect (72). Finally, a strength-based CBT intervention showed significant improvements on distress, on protective factors, and on quality of life in first year psychology students (74). This specific intervention was focused on improving resilience skills, by activating personal strengths and talents.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, distress tolerance was not significant, suggesting that the ability to adapt and overcome long-term challenges may be more relevant than the ability to cope with acute frustrations. Therefore, resilience-focused interventions using cognitive-behavioral therapy (CBT), mindfulness training, or a combination of both may be of particular benefit to patients during the pandemic [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%